Biomarkers in Drug Hypersensitivity - Emanuela Corsini (Frontiers Research Topics, 2017)
Biomarkers, especially those based on pharmacogenomics testing, have proved to be extremely useful for type A adverse drug reactions. Clinical practice guidelines based on biomarker testing are presently being developed and updated for type A adverse drug reactions. In contrast, little attention has been paid to the potential use of biomarkers in type B adverse reactions, characterized by the occurrence of reactions not directly related to the pharmacological properties of the drug. Drug-induced hypersensitivity belongs to those type B reactions. Drug-induced hypersensitivity reactions involve complex mechanisms that include, among others, the metabolic activation and haptenization of drug metabolites. Hence, factors that influence the pharmacokinetics of drug and metabolites may contribute to the development of some drug-induced hypersensitivity reactions. This implies that processes such as ADME (absorption, distribution, metabolism and excretion) that are typically involved in type A adverse drug reactions, may have a role in hypersensitivity reactions too. In addition to metabolic activation, several signal transduction pathways participate and modulate the development and the clinical presentation of drug hypersensitivity. The diverse mechanisms underlying such drug-hypersensitivity reactions lead to four major groups of reactions according to the Gell and Coombs classification: immediate, cytotoxic, immune complex and delayed. The enormous complexity of drug-hypersensitivity reactions is a consequence of the variety of mechanisms involved, which may be related, among others, to drug metabolism, generation of antigenic signals, stimulation and maturation of dendritic cells, presentation of haptens and mechanisms of cytotoxicity. In addition, a plethora of possible clinical presentations exists, including urticaria, angioedema, anaphylaxis, cytopenias, nephritis, serum sickness, vasculitis, contact dermatitis, drug rash, eosinophilia and systemic symptoms, Stevens-Johnson syndrome, toxic epidermal necrolysis and acute generalized exanthematous pustulosis. The rapid progress in the field in recent years indicates that the combination of several disciplines is essential to understand the mechanisms involved in this particular, and not completely understood, type of adverse drug reactions. The objective of this Research Topic is to present insights obtained from both basic and clinical scientists, which may include studies related to the identification, validation, refinement and clinical implementation of biomarkers for drug-induced hypersensitivity. The Topic aims to include recent findings related, but not limited to, potential phenomic, genomic, proteomic, metabolomic and signal transduction biomarkers. These biomarkers could eventually be used in clinical practice and/or these might contribute, as a proof of concept, to our understanding of the complex events leading to drug hypersensitivity reactions. In addition the Topic will cover recent developments and methodological advances in the diagnosis, prevention and therapeutic management of drug-induced hypersensitivity.